2016
DOI: 10.1371/journal.pone.0157324
|View full text |Cite
|
Sign up to set email alerts
|

Putting PrEP into Practice: Lessons Learned from Early-Adopting U.S. Providers’ Firsthand Experiences Providing HIV Pre-Exposure Prophylaxis and Associated Care

Abstract: Optimizing access to HIV pre-exposure prophylaxis (PrEP), an evidence-based HIV prevention resource, requires expanding healthcare providers’ adoption of PrEP into clinical practice. This qualitative study explored PrEP providers’ firsthand experiences relative to six commonly-cited barriers to prescription—financial coverage, implementation logistics, eligibility determination, adherence concerns, side effects, and anticipated behavior change (risk compensation)—as well as their recommendations for training P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 18 publications
4
96
0
5
Order By: Relevance
“…This also suggests that the anticipated burden of barriers to prescribing PrEP is greater than what providers experience once they actually prescribe it. Thus, interventions promoting PrEP among providers may be more successful by addressing each barrier specifically and perhaps by presenting data from this and other studies [33] suggesting that the burden of these barriers is lower among providers who actually prescribe PrEP. The most prevalent concern or negative attitude toward PrEP was the thought that patients should use condoms instead of PrEP, an idea endorsed by about one-third of the sample.…”
Section: Discussionmentioning
confidence: 89%
“…This also suggests that the anticipated burden of barriers to prescribing PrEP is greater than what providers experience once they actually prescribe it. Thus, interventions promoting PrEP among providers may be more successful by addressing each barrier specifically and perhaps by presenting data from this and other studies [33] suggesting that the burden of these barriers is lower among providers who actually prescribe PrEP. The most prevalent concern or negative attitude toward PrEP was the thought that patients should use condoms instead of PrEP, an idea endorsed by about one-third of the sample.…”
Section: Discussionmentioning
confidence: 89%
“…In theory, the target for PrEP persistence is simple: individuals should take PrEP as long as they are at risk for HIV, a PrEP IMPACT concept known as prevention-effective adherence [36]. However, this concept can be challenging to put in practice for individuals (as mapping risk may be difficult for both PrEP users and providers) and for programmes (since measuring use and risk periods may be difficult to measure and track at scale); financial and systematic barriers may also impede patients from achieving their desired persistence [42][43][44]. For individuals, risk should be considered in terms of periods or seasons, not days or weeks [45]; thus, we suggest an expectation of six months of use, while not a perfect fit for all PrEP users, might be useful for programme evaluation and good habit development [46].…”
Section: Expectations For Persistencementioning
confidence: 99%
“…Some providers have applied this score in their clinical practice [51], but use of this and other risk assessment tools is not widespread. Other international guidelines do not utilize a risk score, but provide criteria to identify which MSM and transgender women are at greatest risk [52, 53].…”
Section: Emerging Challengesmentioning
confidence: 99%
“…A qualitative study with Black MSM in New York City to assess barriers to utilizing PrEP found that participants felt mistrustful of and disempowered by health care providers when discussing sexual health histories and HIV prevention options, and that a recommendation to use PrEP would not be sufficiently compelling for them to initiate PrEP [124]. These results indicate a need to train providers in how to conduct patient-centered, nonjudgmental sexual health histories and discussions about PrEP, which would ideally include elements of rigorously tested, culturally-tailored prevention messages about PrEP for disenfranchised populations [51] and clear communication of acceptance towards LGBT individuals.…”
Section: Emerging Challengesmentioning
confidence: 99%